KEMAJUAN TEKNOLOGI INFORMASI DALAM KAITANNYA DENGAN PERMOHONAN PEROLEHAN STATUS BADAN HUKUM PERSEROAN - Wiriasih, I Made; Dalem Dahana, Cokorda (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
Advancement in technological period makes easy for the Company, to obtain the approval status of legal entity through a notary public as the authorities made the deed of incorporation of Company. Through Sisminbakum or legal administrative system online in cyberspace. Since the passage of the Minister of Justice and Human Rights of the Republic Indonesia Number: M-01. HT. 1:01 TH 2000 on the Application of Legal Administration at the Directorate General of the General Administrative Department of Justice and Human Rights of the Republic Indonesia, the notary can directly access the Ministry of Justice and Human Rights electronically.
Keywords: KEMAJUAN TEKNOLOGI INFORMASI DALAM KAITANNYA DENGAN PERMOHONAN PEROLEHAN STATUS BADAN HUKUM PERSEROAN